Repeating fast radio bursts from collapses of the crust of a strange star - Jinjun Geng (Elsevier, 2021)
Summary: Strange stars (SSs) are compact objects made of deconfined quarks. It is hard to distinguish SSs from neutron stars as a thin crust composed of normal hadronic matter may exist and obscure the whole surface of the SS. Here we suggest that the intriguing repeating fast radio bursts (FRBs) are produced by the intermittent fractional collapses of the crust of an SS induced by refilling of materials accreted from its low-mass companion. The periodic/sporadic/clustered temporal behaviors of FRBs could be well understood in our scenario. Especially, the periodicity is attributed to the modulation of accretion rate through the disk instabilities. To account for a ~16-day periodicity of the repeating FRB source of 180916.J0158+65, a Shakura-Sunyaev disk with a viscosity parameter of 0.004 and an accretion rate of 3 × 1016 g s−1 is invoked. Our scenario, if favored by future observations, will serve as indirect evidence for the strange quark matter hypothesis. Public summary: • Strange quark stars are extremely compact objects mainly composed of u, d, and s quarks • Fractional collapse of the crust of a strange quark star can explain the repeating FRB 180916 • Materials accreted from the companion star accumulate at the polar region and trigger the local collapse • The 16-day periodicity of FRB 180916 originates from the thermal-viscous instability of the accretion disk, and the active window corresponds to a high accretion state of the system